THINK PAIR SHARE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 1 PURWOSARI TAHUN PELAJARAN 2013/2014 - Suryanti, Alis (AKSIOMA JURNAL PENDIDIKAN MATEMATIKA, 2015)
The aims of this research were to increase the activity and study result of student by implementation of Cooperative Learning Tipe Think Pair Share. The method of the research was Classroom Action Reserach. The instrument of data collection used observation sheet, formatif test sheet, and documentation. Technique of data analysis used qualitative and quantitative analysis. The result showed that the student activity in cycle I 52,91% (Moderately Active),in cycle II 63,24% (Active) to be 77,49% (Active) in cycle III. Percentage of the study completeness in cycle I 57,44%, in cycle II 70,22% to be 85,11% in cycle III.